Exploring the potential of lactic acid bacteria to produce postbiotics with antimicrobial and antioxidant properties: focus on the probiotic strain Pediococcus pentosaceus RC007 for industrial-scale production - Rosales Cavaglieri, Lorenzo Antonio (2025)
Bioprospection of natural compounds by next-generation probiotic strains holds immense promise for promoting beneficial effects on both animal and human health. The aim of this work was to study the antimicrobial activity of lactic acid bacteria (LAB) postbiotics on multidrug-resistant pathogenic Salmonella sp. and Escherichia coli. Moreover, short-chain fatty acids (SCFAs) production and the postbiotics antioxidant activity were evaluated. Additionally, the potential for industrial-scale production to ensure feasibility andscalability of postbiotic-based applications was determined. LAB strains inhibited E. coli O157:H7 and Pediococcus pentosaceus showed the strongest inhibition. Among SCFA, the highest acetic and lactic acid concentrations were 41.91 and 181.52 mM, respectively. Thehighest ABTS+ Trolox equivalent and ferric-reducing antioxidant power values were 31.47 μg Trolox/g after 24 hr and 11.38 μmol/g after 48 hr, respectively. There was no statistically significant difference between fermentation times. Industrial-scale production of P.  pentosaceus RC007 showed the specific growth rate as a kinetic parameter and the biomass production as a productive parameter; they were 1.99 hr −1 and 1.1 g/L, respectively. The maximum production point was reached at pH 4. P. pentosaceus RC007canbeconsideredagood candidate to scale up considering its probiotic properties and the large amount of postbiotic metabolites of interest in health and industrial purposes.